Voluntary Disclosure When Information Quality Is Unknown - Kim, Eunhee; Pae, Suil (The Accounting Review, 2025)
ABSTRACT This paper presents a costly voluntary disclosure model in which the information quality of a signal about a firm’s future cash flow is unknown, where the information quality, also called signal quality, refers to signal precision. Disclosure plays a dual role in firm valuation, providing information about both the cash flow and signal quality. We identify a necessary and sufficient condition under which the firm price under disclosure is a nonmonotonic and bounded function of the signal. Under this condition, as the disclosure cost increases, the equilibrium changes from an intermediate pool of undisclosed signals to a low-end pool of undisclosed signals, to two disjoint pools of undisclosed signals, and finally to no disclosure. Our results remain qualitatively unchanged when the firm may or may not have private information. Overall, this study offers alternative explanations for the empirical findings of why some firms disclose (withhold) seemingly bad (good) news. JEL Classifications: D61; G14; M41.